Impact of 25-Hydroxy Vitamin D on White Matter Hyperintensity in Elderly Patients: A Systematic Review and Meta-Analysis - Zhao, Yilei; Xu, Jingfeng; Feng, Zhan; Wang, Jincheng (Frontiers in Neurology, 2022)
Some studies show that low serum vitamin D levels are associated with white matter hyperintensity (WMH）, while other studies report no association. This meta-analysis aimed to investigate the presence of an association between serum 25-hydroxy vitamin D [25(OH)D] levels andWMH. PubMed, Embase, the Cochrane Library, CNKI, WANFANG, and VIP were searched for available papers published up to December 2020. The outcomes were the odds ratios (ORs) with 95% confidence intervals (CIs) for the association between different vitamin D statuses andWMH. All meta-analyses were performed using a random-effects model. Five studies (4393 patients) were included. Compared with sufficient 25(OH)D levels, 25(OH)D deficiency was not associated with WMH(OR=1.67, 95%CI: 0.92-3.04; I2=70.2%, Pheterogeneity=0.009), nor was 25(OH)D insufficiency (OR=1.21, 95%CI: 0.89-1.65; I2=48.1%, Pheterogeneity=0.103) (Figure 3). A decrease of 25 nmol/L in 25(OH)D levels was associated with WMH(OR=1.83, 95%CI: 1.34-2.49; I2=0%, Pheterogeneity=0.512). The sensitivity analyses showed that the results were robust. 25(OH)D deficiency and insufficiency are not associated withWMH. A decrease of 25 nmol/L in 25(OH)D levels was associated withWMH, but this result will have to be confirmed. Prospective trials, both cross-sectional and longitudinal, are necessary to examine the association between 25(OH)D levels andWMH.